Presupposition in Political Memes: A Cyber-Pragmatic Approach to Indonesian Politics - Sufi, M. Iqbal Farabi; Putri, Dian Marisha (Universitas Muhammadiyah Lampung, 2026)
Despite the growing use of internet memes in political discourse on social media, the pragmatic mechanisms through which they construct implicit meaning remain insufficiently explored, particularly in the context of presupposition. While existing studies have examined memes as forms of digital culture, rhetoric, or discourse, limited attention has been given to how presupposition functions as a strategy for embedding ideological assumptions in political memes. This study aims to examine the use of presupposition in Indonesian political memes and to analyze how these presuppositions function as pragmatic strategies for conveying implicit political critique in digital discourse. The research employs a qualitative descriptive method to analyze six political memes collected from Facebook, Instagram, and WhatsApp through purposive sampling based on their political relevance and multimodal characteristics. Data were collected using a documentary method and analyzed using Yule’s (1996) presupposition typology, Yus’s (2011) cyber-pragmatic framework, and Fairclough’s (2013) discourse perspective. The findings reveal that existential, lexical, structural, and counterfactual presuppositions are used to encode implicit assumptions about political actors, institutions, and events. These presuppositions rely on shared background knowledge, enabling meme creators to express satire and ideological critique indirectly. The study concludes that presupposition functions as an important pragmatic mechanism that allows political memes to communicate criticism and ideological positioning within Indonesia’s digital public sphere. This study contributes to the field of digital pragmatics by highlighting presupposition as a key analytical lens for understanding how implicit meaning and ideology are constructed in multimodal political communication on social media.